The incidence and pattern of non-odontogenic orofacial pain conditions at a tertiary hospital in Tanzania - Hirani, Vanisha Aroon; Owibingire, Sira Stanslaus; Moshy, Jeremiah Robert; Sohal, Karpal Singh (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Non-odontogenic orofacial pain (NOFP) is a result of pathology, or injury to the structures in the orofacial region including the muscles, temporomandibular joint, neurovascular structures, and glands. This multi-diverse aetiopathogenesis poses a challenge in the diagnosis and management of NOPF. To determine the incidence and trend of various non-odontogenic orofacial pain conditions at a tertiary hospital in Tanzania. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This cross-sectional study was conducted at the Muhimbili National Hospital (MNH) for 6 months. The information gathered included socio-demographic characteristics of participants, characteristics of pain, and cause of pain. Pain intensity was assessed using the Visual Analogue Scale (VAS). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The incidence of NOFP was 3.3%. The male to female ratio was 1.7:1 and the mean age of patients was 44.2 ± 17.4 years. The mean intensity of the pain using the VAS was 47.27 ± 5.66. Most (36.7%) patients experienced sharp pain. The common causes of NOFP were trauma (43.3%) and malignant lesions (38.3%). A statistically significant association between the age and sex of the patients and the causes of non-odontogenic pain was observed (p < 0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The incidence of non-odontogenic orofacial pain is low. Trauma and malignant conditions were the leading causes of NOFP.